Testing-based process for component substitutability - Flores, Andrés Pablo (2012)
Software components have emerged to ease the assembly of software systems. However, updates of systems by substitution or upgrades of components demand careful management due to stability risks of deployed systems. Replacement components must be properly evaluated to identify if they provide the expected behaviour affected by substitution. To address this problem, this paper proposes a substitutability assessment process in which the regular compatibility analysis is complemented with the use of black-box testing criteria. The purpose is to observe the components' behaviour by analysing their internal functions of data transformation, which fulfils the observability testing metric. The approach is conceptually based on the technique Back-to-Back testing. When a component should be replaced, a specific Test Suite TS is built in order to represent its behavioural facets, viz. a Component Behaviour TS. This TS is later exercised on candidate upgrades or replacement components with the purpose of identifying the required compatibility. Automation of the process is supported through the testooj tool, which constrains the conditions and steps of the whole process in order to provide a rigorous and reliable approach.